OXYGEN ISOTOPE FRACTIONATION BETWEEN ZIRCON AND WATER: EXPERIMENTAL DETERMINATION AND COMPARISON WITH QUARTZ-ZIRCON CALIBRATIONS - Krylov D.P.; Zagnitko V.N.; Hoernes S.; Lugovaja I.P.; Hoffbauer R. (My University, 2002)
Oxygen isotope fractionation between synthesised zircon and water has been experimentally quantified at 700, 800, 900, and 1000°C. The results are interpolated by: Delta(zrn-H2O) = -3.70 + 2.74 +/- 0.19 x(2), where x = 10(3)/T (K). Combined with the fractionation between quartz and water (Bottinga & Javoy, 1973) this yields: Delta(qtz-zrn) = 1.36 x(2). Theoretical evaluations of the reduced partition function ratios for zircon and two (alpha- and beta-) modifications of quartz are expressed in terms of the following polynomials: 1000 lnf(zm) = 8.3 3 06 x(2) + 1.9402 x - 0.6896 (400 < T < 1100°C) 1000 lnf(alpha-qtz) = 7.8963 x(2) + 7.4091 x - 3.6015 (200°C < T < alpha-quartz stability field) 1000 lnf(beta-qtz) = 9.3362 x(2) + 2.4514 x - 0.7844 (beta-quartz stability field up to 1100°C). These expressions are in excellent agreement both with the experimentally derived factors of oxygen isotope fractionation for beta-quartz and zircon, and the incremental calibrations for alpha-quartz and zircon (Hoffbauer et al., 1994). The effect of alpha-beta-quartz transition on oxygen isotope fractionation implies, that those calculations, anchored to the theoretically evaluated reduced partition function ratios of quartz (e.g., Zheng, 1993), can predict fractionations only within the P-T stability field of the respective modification of quartz (i.e. alpha-quartz).
Keywords: oxygen isotopes; zircon water fractionation; quartz; geothermometry